Efektivitas KALPIN dan Leaflet dalam Meningkatkan Self-Efficacy Penderita Hipertensi - Arvida Bar; Kaimuddin Kaimuddin; M. Ridwan (Journal of Telenursing (JOTING), 2022)
This study aims to determine the effectiveness of KALPIN (Smart Calendar) and leaflets in increasing self-efficacy in hypertensive patients. The method used is a quasi-experimental with a pretest-posttest control group design involving 100 patients undergoing outpatient treatment at the Penyengat Olak Health Center. The results showed that the average value of respondents' self-efficacy before being given intervention in the intervention group was 5.8 with a standard deviation of 4.638, while the average value after being given intervention was 9.89 with a standard deviation of 1.526. Meanwhile, the average self-efficacy before intervention in the control group was 6.37 with a standard deviation of 3.774, while the average value after intervention in the control group was 7.00 with a standard deviation of 3.058. The results of further analysis using the Wilcoxon test obtained a p-value of <0.05. In conclusion, there was an increase in the self-efficacy of hypertension sufferers after giving KALPIN education and leaflets. Keywords: Hypertension, KALPIN, Leaflet, Self-Efficacy